How medium sized enterprises price products in international industrial markets : case study of LIKO AB - Danielsson, Max; Stolt, Ted (2003)
Due to our interest in pricing and the fact that export pricing has more or less been neglected by academic research, we found it interesting to write a thesis regarding this area. The purpose of the thesis in general is to gain a better understanding of export pricing of industrial products by medium sized enterprises. We have narrowed this problem area down to examining factors influencing export pricing, and how the implemented pricing strategies can be described. We conducted the case study on LIKO AB, a company situated close to Luleå, Sweden. We found that different factors influencing export pricing have different impact on the choice of pricing strategy. Costs, gross margin required by senior management and management attitudes were some of the most important factors. Furthermore we concluded that several pricing strategies are used simultaneously. Validerat; 20101217 (root)